Predictable Values of Decompressive Craniectomy in Patients with Acute Subdural Hematoma: Comparison between Decompressive Craniectomy after Craniotomy Group and Craniotomy Only Group - Kim, Hyunjun; Suh, Sang-Jun; Kang, Ho-Jun; Lee, Min-Seok; Lee, Yoon-Soo; Lee, Jeong-Ho; Kang, Dong-Gee (Korean journal of neurotrauma, 2018)
Patients with traumatic acute subdural hematoma (ASDH) often require surgical treatment. Among patients who primarily underwent craniotomy for the removal of hematoma, some consequently developed aggressive intracranial hypertension and brain edema, and required secondary decompressive craniectomy (DC). To avoid reoperation, we investigated factors which predict the requirement of DC by comparing groups of ASDH patients who did and did not require DC after craniotomy. The 129 patients with ASDH who underwent craniotomy from September 2007 to September 2017 were reviewed. Among these patients, 19 patients who needed additional DC (group A) and 105 patients who underwent primary craniotomy only without reoperation (group B) were evaluated. A total of 17 preoperative and intraoperative factors were analyzed and compared statistically. Univariate and multivariate analyses were used to compare these factors. Five factors showed significant differences between the two groups. They were the length of midline shifting to maximal subdural hematoma thickness ratio (magnetization transfer [MT] ratio) greater than 1 ( <0.001), coexistence of intraventricular hemorrhage (IVH) ( <0.001), traumatic intracerebral hemorrhage (TICH) ( =0.001), intraoperative findings showing intracranial hypertension combined with brain edema ( <0.001), and bleeding tendency ( =0.02). An average value of 2.74±1.52 was obtained for these factors for group A, which was significantly different from that for group B ( <0.001). An MT ratio >1, IVH, and TICH on preoperative brain computed tomography images, intraoperative signs of intracranial hypertension, brain edema, and bleeding tendency were identified as factors indicating that DC would be required. The necessity for preemptive DC must be carefully considered in patients with such risk factors.